Time-Dependent Ultimate Strength Performance of Corroded FPSOs - Kim, D.K. (Springer Verlag, 2014)
Recently, various types of offshore structures are built and constructed to fulfil the high demand of ocean exploration especially in oil and gas industry. In this regards, the deep-water area is becoming more and more important field for exploration activity. Floating production storage and offloading (FPSO) is one of the popular structures used to exploit the sources of oil and gas in subsea area. Basically, FPSO is exposed to ocean environment and thus faces age-related problems such as corrosion damage. In the present study, the time-dependent effect of corrosion wastage on the ultimate limit state-based structural safety assessments of three FPSOs was performed. An empirical time-dependent corrosion wastage model, which was obtained using real corrosion measurement database, was adopted to predict the progress of corrosion damages. Ultimate strengths of stiffened panels and hull girders for converted FPSOs (single hull type and double hull type) were compared with a new-built FPSO. Important insights obtained from the present study were documented. Â© 2014, King Fahd University of Petroleum and Minerals.